The utility of media-delivered information for Generation Z travelers from Poland in the Covid-19 pandemic - Balińska, Agata; Jaska, Ewa (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: Information and knowledge are economic goods that sustain economic development, including the tourism industry, today. In the past, the tourism sector was affected by various crises, but none of them was as extensive and impacted tourism on a global scale as it has happened now — during the Covid-19 pandemic. Generation Z, which is a cohort of extremely active travelers, mostly rely on digitally-delivered information. New media like the Internet, including social media, enable tourism entities to reach not only local, but also global markets. However, in the studies published so far, social media and the Internet have usually been analyzed as one category, which in the era of changing technologies and the new emerging behaviors of young tourists seems insufficient. Therefore, there is a need to verify the current state of research and determine the new media utility on the tourism market. Aim: The study aims to investigate the capability of new media to meet the information needs of potential Gen Z tourists during the pandemic and to identify the characteristics of useful media information Results: The study involved a desk research and a diagnostic survey method, including the online survey technique. The collected material was analyzed qualitatively and quantitatively. 374 responses were received to the questionnaire. The study was conducted in October 2020. Additionally, an observation, carried out in thematic groups in social media, was used as a complementary technique. The conducted research made it possible to verify the utility of online sources of information used by Gen Z respondents during the pandemic. The study determined the relationships between Gen Z travel frequency, average daily time spent in front of the computer, the amount of tourism expenditure and the utility of new media. The main contribution of this study is the identification of the features of useful media-delivered information about tourism products and services as perceived by Gen Z representatives, which contributes to filling the existing research gap.